Cross‐country skiing movement factorization to explore relationships between skiing economy and athletes' skills. (26th July 2017) - Pellegrini, B.; Zoppirolli, C.; Boccia, G.; Bortolan, L.; Schena, F.
Abstract : We investigated the relationships between the biomechanics of the double poling (DP) technique in cross‐country skiing, its economy, and athletes' skill. To this aim, skiers' motion has been factorized into components through principal component analysis (PCA). Eight high‐level (HL) and eight regional level (RL) male cross‐country skiers performed a 5‐minute submaximal DP trial while roller skiing on a treadmill at 14 km h −1 and 2° incline. Whole‐body kinematics was recorded with a motion capture system. PCA was applied to markers coordinates to extract principal movements (PMk ), which were ranked by their variance. Energy cost (EC) of locomotion was calculated from ergospirometric measurements. Results showed that 96.7%±0.6% of total skiing pattern variance can be described with the first three PMk. (Shoulder and trunk flexion‐extension are described PM1 and PM2 and elbow flexion‐extension are mainly represented in PM2 and PM3. The variance of further components, consisting of residual movements (eg, slow postural changes or high‐frequency vibrations), was greater for the RL than the HL skiers (4.0%±0.5% vs 2.6%±0.3%; P <.001) and was positively correlated with EC ( R 2 =.646; P <.001). PCA permitted to describe the biomechanics of the DP technique through a limited set of principal movements. Skiing skills and economy appeared to be related to a skier's ability to simplify movement complexity, suggesting that an efficient skier is better able to reduce superfluous movement components during DP.